(untitled) (Research, Society and Development, 2022)
Tetragonisca angustula is the stingless bee more managed by beekeepers, whose honey has many medicinal properties and is distributed throughout Latin America. They have variation in color of mesepisternum and can be black, yellow or mixed. They might be classified into two species (T. angustula and T. fiebrigi) or two subspecies (T. angustula angustula and T. angustula fiebrigi). This study aimed study was to analyze the genetic variability of populations T. angustula sampled using the technique simple repeated sequences and to analyze the interaction of molecular markers used in other studies to verify the possible existence of a marker that distinguishes genetically. A total of 60 individuals were sampled in the cities of Maringá, Cianorte and Terra Boa, Paraná state, Southern Brazil. The results showed that all loci are polymorphic. The value of FST=0.1173 shows that populations are moderately differentiated and analysis of molecular variance indicates that 76% of the change occurs within the analyzed populations. The largest value of delta K obtained by Bayesian inference estimated the actual number of people equal to three. The analysis of interaction networks has shown that there are more interactions with isozymes, but none of them allowed separate T. angustula in two species.